Policy Implications for Human Development of Vietnam from the History of HDI - Đại, Nguyễn Văn (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2014)
Abstract: Since the renovation was introduced in 1986 (known as Doi Moi), Vietnam has achieved many great economic successes. The spiritual and material life of the majority of the Vietnamese population has improved over time. Human development process both receives benefits from and affects back upon Doi Moi because of its interactive correlation. The Human Development Index (HDI) measures the achievement of countries in human development, however, this index varies greatly due to economic development. The relative increase of the HDI index of a country compared to others is also the requirement for the progress of a modern society because the components of HDI cover three main dimensions of life. Therefore, the calculation of the component indices of HDI has changed over time, and this affects the ranking of the HDI for various countries, including Vietnam. This research paper shows that Vietnam’s income and education indices are affected negatively by these changes, especially the latter. Human development in Vietnam shows several signs of lagging behind other countries, at least behind those in the Southeast Asian region and China. Therefore, in order to reduce the gap between GNI (Gross National Income) and GDP (Gross Domestic Product) and to increase mean years and expected years of schooling as well, Vietnam needs to focus on the policies of education which can decrease dropout rate and balance educational levels. In addition, a policy for the economy restructuring needs to be adopted to raise the effectiveness of in - depth growth factors. Keywords: Education, economic growth, human development, Human Development Index (HDI).